2019
DOI: 10.3390/ijerph16132268
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Biases of Consumers’ Risk Perception of Foodborne Diseases in China: Examining Anchoring Effect

Abstract: Consumer cognitive biases arise from judgment and decision-making due to their limitations in information processing. As one of the important cognitive biases, the anchoring effect plays a significant role in interfering with consumers’ risk perception. With a stratified random approach, we collected survey data from 375 consumers in Wuxi, Jiangsu Province, China. Based on these data, this study attempted to analyze the anchoring effect in consumers’ risk perception of foodborne diseases (FBDs) and the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
2
18
0
2
Order By: Relevance
“…Besides, a higher uncertainty and coping appraisal may facilitate their protective behavioral intention [8,19]. Moreover, risk perception and coping appraisal have a significant positive effect on information seeking, which conforms to previous studies [27,36]. However, coping appraisal positively influences information seeking, with the opposite direction of the coefficient compared to our hypothesis.…”
Section: Antecedents Of Protective Behavioral Intentionsupporting
confidence: 90%
See 2 more Smart Citations
“…Besides, a higher uncertainty and coping appraisal may facilitate their protective behavioral intention [8,19]. Moreover, risk perception and coping appraisal have a significant positive effect on information seeking, which conforms to previous studies [27,36]. However, coping appraisal positively influences information seeking, with the opposite direction of the coefficient compared to our hypothesis.…”
Section: Antecedents Of Protective Behavioral Intentionsupporting
confidence: 90%
“…Changes in risk perception and CAE will evoke affection responses (usually fear), motivate information demand, and further induce actual information seeking behavior. Shan [36], Zhang [37]), and Terpstra [38] have confirmed that people in risky situations demonstrate more information seeking intentions and behavior. Hovick [11] and Wei [39] demonstrated the indirect and direct effect of risk perception on the information process.…”
Section: Risk Perception and Coping Appraisalmentioning
confidence: 85%
See 1 more Smart Citation
“…Information and education should be provided particularly to young consumers in their 20s, who have low risk perception about chemical products. Providing consumer education should be considered because consumers' risk perception affects public health and personal risk management [30][31][32][33][34]; along with expert opinions, the public's risk perception is an essential element in improving public health and the policy-making process [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…[30] conducted a comprehensive risk assessment analysis associated with establishing a prompt alarm system to prevent or restrict the sale and use of products (e.g., tainted or harmful toys, cosmetics, and chemicals) that pose a serious risk to consumer health and safety. In addition, many studies conducted surveys on consumers' risk perceptions and attitudes toward hazardous products [31][32][33][34]. Those studies found that consumers' risk perception of hazardous products affected their individual risk management in terms of the environment and health as well as their attitude.…”
Section: Introductionmentioning
confidence: 99%